Ownership and utilisation of long lasting insecticide treated nets following free distribution campaign in South West Nigeria - Aderibigbe, Sunday Adedeji (The African Field Epidemiology Network, 2014)
INTRODUCTION: Malaria has proven to be the most horrendous and intractable amongst the health problems confronting countries in the sub-Saharan Africa. This study aims to determine the ownership and utilisation of long lasting insecticide treated nets following free distribution campaign in a state in South West Nigeria. METHODS: Multi-stage sampling technique was used to recruit 2560 households spread across the 16 LGAs of the state. Interviewer administered standardized questionnaire was used for the survey. Data analysis was done using Stata 10 software. RESULTS: Sixty eight point six percent (68.6%) of the households had at least one under-five child living in the household while 32.6% had at least one pregnant woman living in the household. A total of 2440 (95.3%) households received LLIN during the campaign. Overall, the utilization rate for all respondents was 58.5%. Despite the fact that 2440 households received LLINs during the campaign, only 84.3% of them were seen to have hung theirs during the survey. CONCLUSION: Coverage and ownership of LLINs increased significantly following the free distribution campaign. There was a discrepancy between net possession and net use with rate of use lower than possession. Post distribution educational campaign should be incorporated into future distribution campaigns to help increase net utilisation.